Estrat??gias para o enfrentamento do absente??smo dos usu??rios em consultas odontol??gicas em um hospital militar de administra????o direta - Concei????o Junior, Alberto Boaventura da (2020)
The accessibility and use of the dental services in a Military Hospital of Direct Administration, behind in its essence, is an important challenge for managers: it corresponds to the users expectations in conducting a good standard of care and favors the continuous health promotion. One of the biggest challenges faced by managing the Institution corresponds to the lack of resources caused by previously scheduled patients??? absence, which also contributes with the lower quality of the services from the patients??? perspective. In this way, in the face of these challenges regarding constantly improving oral health services provided in the public sector, this study aimed to analyze the causes of absence in the dental clinic located at a public hospital located at Sao Paulo city - SP, Brazil, and studied the possible strategies for its reduction. In addition, absenteeism rates can be quantified in outpatient activities of dental specialties and track applications for improving the provision of services offered. The methodology used during this study is descriptive and analytical, with a cross-sectional design, introduced as action research workshops for a better implementation of agenda management. The study was carried out in two phases: 1st ??? analysis and quantification of the reasons for the absence from outpatient dental consultations; and 2nd _ implementation of action research workshops. Among the main results, it was identified that the main reason for absenteeism was due to the participants??? forgetfulness. Based on it, the participants of the action research workshops suggested that patients are notified in advance of the consultation in order to avoid absences. In addition, a scheduling deselection channel was implemented as a strategy to reduce absenteeism.